FRI0376 Mechanism of Phenotype Conversion from Rheumatoid Arthritis to Lupus in FCᴦRIIB-Deficient C57BL/6 YAA Mice. (9th June 2015) - Kawano, S.; Amano, H.; Lin, Q.; Nishikawa, K.; Tsurui, H.T.; Shirai, T.; Hirose, S.; Takasaki, Y.
Abstract : Background: We previously obtained a FcγRIIB-deficient C57BL/6 (B6) congenic strain of mice, which spontaneously developed severe rheumatoid arthritis (RA). The introduction of the Yaa ( Y-linked autoimmune acceleration ) mutation, which is a consequence of a translocation from the telomeric end of the X chromosome containing the Tlr7 gene onto the Y chromosome, to the FcγRIIB-deficient B6 (B6.FcγRIIB -/- . Yaa ) mice developed lupus like nephritis but not RA. This phenotype conversion did not depend on autoantibody specificity, since the mice showed a marked increase in serum levels of both lupus-related and RA related autoantibodies. Objectives: To examine the mechanism of the disease phenotype conversion from RA (B6.FcγRIIB -/- mice) to lupus (B6.FcγRIIB -/- . Yaa mice), we compared subpopulations of peripheral blood mononuclear cells and spleen cells, also cytokine expression of stimulated spleen cells. Methods: Peripheral blood mononuclear cells were analyzed by flow cytometry and two distinct subpopulation of Gr-1 positive and negative monocytes were analyzed among B6, B6. Yaa, B6.FcγRIIB -/-, and B6.FcγRIIB -/- . Yaa mice at 2 months of age. Comparisons of cell surface phenotypes of splenic lymphocytes were analyzed using flow cytometry. Spleen cells were triple-stained and the frequency of marginal zone (MZ) B cells, activation/maturation status of B cells, peanut agglutinin (PNA) + germinal center (GC) B cells, and CD138 + plasma cells were analyzed. Also activation/maturation status of T cells, PD1 + ICOS + CD4 + and PD1 + CXCR5 + CD4 + follicular helper T cells were analyzed. Quantitative real-time PCR analysis was performed to compare mRNA expression levels of notable cytokines in spleen between B6.FcγRIIB -/- and B6.FcγRIIB -/- . Yaa mice at 4 months of age. PMA/ionomycin-stimulated spleen cells from these mice were also analyzed by flow cytometry. Results: Flow cytometric analysis of peripheral blood monocytes from 2-month-old mice revealed monocytosis in B6.FcγRIIB -/- . Yaa mice but not in B6.FcγRIIB -/- mice. The frequency of Gr-1 - "resident" monocytes was increased in B6.FcγRIIB -/- . Yaa mice. Flow cytometric analysis of spleen cells from 4-month-old mice revealed that, while there were no differences in frequencies of B220 + B cells per total spleen cells among four strains, there was a significant decrease in frequencies of CD21 + CD23 - marginal zone B cells in B6. Yaa and B6.FcγRIIB -/- . Yaa mice. As for the activation/maturation status of B cells, frequencies of CD69 + activated B cells, PNA + GC B cells, and CD138 + plasma cells were significantly higher in B6.FcγRIIB -/- . Yaa mice than those found in other strains of mice. As for T cells, the frequency of CD69 + activated T cells was markedly increased in B6.FcγRIIB -/- . Yaa mice. As for about comparisons of cytokine synthesis, the expression of IL-6, IL-10 and IL-21 were up regulated in B6.FcγRIIB -/- . Yaa mice. Both IL-10 and IL-21 were secreted from CD4 + T cells and the frequencies of IL-10 and IL-21-secreting cells per total CD4 + T cells were significantly higher in B6.FcγRIIB -/- . Yaa mice than those in B6.FcγRIIB -/- mice. Conclusions: The present studies suggest that the mechanism of the disease phenotype conversion from RA to lupus was likely to be due to the activation of monocytes, B cells and T cells leading to the change in cytokine milieus from the activated follicular helper T cells. Disclosure of Interest: None declared